David Underdown, Royalist Conspirators and the Character of English Politics - Bowen, Lloyd (History compass, 2013)
This article discusses David Underdown's first major publication, Royalist Conspiracy in England, 1649-60 (1960). This volume is located in its historiographical context, and it is suggested that commentators have overlooked the potential influence of the Tory historian Sir Keith Feiling on this work, alongside the better known perspectives of Underdown's supervisor, Christopher Hill. Underdown's critical view of royalist conspiracy in this book is discussed through several interpretative categories including political faction, collective biography, emotion and rationality, youth and leadership, tradition and modernity. It is argued that Underdown's approach to royalism became more positive and socially expansive in later publications, but that his view of a persistent moderate and conservative centre ground of early modern political life forms a continuous thread throughout his published work.